Impact of paper and cardboard suppression on OFMSW anaerobic digestion. (October 2016) - Fonoll, X.; Astals, S.; Dosta, J.; Mata-Alvarez, J.
Highlights: Waste paper removal increased OFMSW biodegradability and methane yield. Larger waste degradation annulled expected CH4 losses when halving waste paper load. Digester stability and digestate quality decreased after paper segregation. Waste biodegradability cannot compensate methane losses if all paper is removed. Abstract: Mechanical-biological treatment plants treat municipal solid waste to recover recyclable materials, nutrients and energy. Waste paper and cardboard (WP), the second main compound in municipal solid waste (∼30% in weight basis), is typically used for biogas generation. However, its recovery is gaining attention as it can be used to produce add-value products like bioethanol and residual derived fuel. Nevertheless, WP suppression or replacement will impact anaerobic digestion in terms of biogas production, process stability and digestate management. Two lab-scale reactors were used to assess the impact of WP in anaerobic digestion performance. A control reactor was only fed with biowaste (BioW), while a second reactor was fed with two different mixtures of BioW and WP, i.e. 85/15% and 70/30% (weight basis). Results indicate that either replacing half of the WP by BioW or removing half of the WP has little impact on the methane production. When removing half of the WP, methane production could be sustained by a larger waste biodegradability. The replacement of all WP by BioW increased the reactor methane production (∼37%), while removing all WP would have reduced the methane production about 15%. Finally, replacing WP loading rate by BioW led to a system less tolerant to instability periods and with poorer digestate quality.